2009
DOI: 10.1029/2009ja014125
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial evolution of the solar energetic particle event on 20 January 2005 and resulting radiation doses in aviation

Abstract: [1] The solar energetic particle event on 20 January 2005 was one of the largest ground level events ever observed. Neutron monitor stations in the Antarctic recorded count rate increases of several thousand percent caused by secondary energetic particles, and it took more than 36 h to return to background level. Such huge increases in high energetic solar cosmic radiation on the ground are obviously accompanied by considerable changes in the radiation environment at aviation altitudes. Measurements of 28 neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 50 publications
7
67
0
4
Order By: Relevance
“…Tylka and Dietrich 2009;Matthiä et al 2009). Even for simpler quantities such as the onset time and peak flux, it is important to find a NM whose asymptotic look angle is nearly aligned with the interplanetary magnetic field.…”
Section: Problems In Defining and Characterizing Glesmentioning
confidence: 99%
“…Tylka and Dietrich 2009;Matthiä et al 2009). Even for simpler quantities such as the onset time and peak flux, it is important to find a NM whose asymptotic look angle is nearly aligned with the interplanetary magnetic field.…”
Section: Problems In Defining and Characterizing Glesmentioning
confidence: 99%
“…Several investigators (e.g. Orus et al, 2007;Sreeja et al, 2009;Kane, 2009;Matthiä et al, 2009;McKenna-Lawlor et al, 2010) have studied different aspects associated with the geomagnetic storm or geomagnetic disturbed period around the third week of January 2005. Du et al (2008) have investigated the storm on 21-22 January 2005 and called it an "anomalous" geomagnetic storm as the storm main phase occurs during northward interplanetary magnetic fields (IMFs).…”
Section: Introductionmentioning
confidence: 99%
“…The most energetic events can be observed even at ground-based neutron monitors, and are called ground-level enhancements (GLE) (Forbush, 1946). Recently, Matthia et al (2009a) reported that the effective dose rate at a conventional flight altitude of 40 kft (∼ 12 km) reached 1.0 mSv h −1 during the largest GLE-69 during solar cycle 23. The total effective dose at flight altitude has been estimated for all of the GLE events during solar cycle 23, and ranged from 2.0 µSv to 0.3 mSv (Shea and Smart, 2012).…”
Section: Introductionmentioning
confidence: 99%